Who uses Tinder?: The Dark Triad traits, attachment, and mate value - Jonason, Peter; Bulyk, Rachel (Studia Psychologica: Theoria et praxis, 2019)
Modern dating life has been changed with the advent of smartphone-based applications like Tinder. One way to identify who uses these applications is to compare the personality traits of users to non-users. In two brief studies (N = 581) we compared Tinder-users to non-users in individual differences associated with short-term mating (i.e., psychopathy, Machiavellianism, narcissism [the Dark Triad traits], and anxious attachment) and mate value. We revealed that the men who were Tinder users were especially high in psychopathy and narcissism and women who were Tinder users were especially high in anxious attachment and rated themselves as unsuccessful in finding relationship partners. While exploratory in nature, we suggest that men who are characterized by antisocial traits may use Tinder for opportunistic mating goals whereas women who have struggled to find relationships may use Tinder as a compensatory mating tactic.